Data Warehouse Design for Hospital Executive information using the Facts Constellation Method (Case Study Bali Mandara Eye Hospital) - Dharma, I Gusti Ngurah Aditya; Saputra, Komang Oka; Sastra, Nyoman Putra (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - DecemberDO - 10.24843/IJEET.2020.v05.i02.p02, 2020)
In the development of information technology, it is very important for the industry to create a structured data warehouse. It has functions as a track record data and digital archiving. One industry that requires a data warehouse is a hospital. Hospitals need a digitizing system that can store medical record data and other vital data in their managerial system. Hospitals are now required to have a hospital management information system as an information medium to speed up the process of obtaining computerized information. Hospital data warehouse must be built with a systematic, tactical scheme in reporting and can guarantee its confidentiality from unauthorized persons. Displaying reports from the database is possible but has complex and very slow queries. So to make an executive report that quickly requires making dimensional data warehouse. Data warehouse schemes from a good Hospital Management System can be made in various ways, one of which utilizes the Facts Constellation scheme as the research raised by this paper.